A Web Navigation Frame Work to Identify the Influence of Faculty on Students Using Datamining Tecniques (International Journal of Engineering and Computer Science, 2017)
Analyzing student web browsing behavior is a challenging task. This paper mainly focuses on a methodology to identify the influencing factor that has driven a student towards navigating a particular web site. Most of the research in this direction is untouched to estimate the influence of faculty on the student’s behavioral patterns. In this work we focus on a novel statistical approach based on adaptive Gaussian mixture model, where the data clustered is given as input to the model to classify the student navigating pattern. The concept of regression analysis is used to find the relationship between student’s navigational behavior and faculty’s experience and rating. This article considers a real time dataset of GITAM University for experimentation.